2017
DOI: 10.1002/acm2.12081
|View full text |Cite
|
Sign up to set email alerts
|

Insight gained from responses to surveys on reference dosimetry practices

Abstract: PurposeTo present the results and discuss potential insights gained through surveys on reference dosimetry practices.MethodsTwo surveys were sent to medical physicists to learn about the current state of reference dosimetry practices at radiation oncology clinics worldwide. A short survey designed to maximize response rate was made publicly available and distributed via the AAPM website and a medical physics list server. Another, much more involved survey, was sent to a smaller group of physicists to gain insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It is worth noting that in a recent survey on reference dosimetry practices about 40% of respondents used the PTW 30013 chamber for reference dosimetry of MV photon beams, making it the most commonly used chamber for these measurements. 8 Since the ICRU-90 recommendations are relevant only for graphite and water, results for these representative chambers will demonstrate the impacts of ICRU-90 on k Q factors. The EGSnrc Monte Carlo simulation toolkit 9 is used to model the transport of electrons and photons in matter and estimate the energy deposited in regions of interest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that in a recent survey on reference dosimetry practices about 40% of respondents used the PTW 30013 chamber for reference dosimetry of MV photon beams, making it the most commonly used chamber for these measurements. 8 Since the ICRU-90 recommendations are relevant only for graphite and water, results for these representative chambers will demonstrate the impacts of ICRU-90 on k Q factors. The EGSnrc Monte Carlo simulation toolkit 9 is used to model the transport of electrons and photons in matter and estimate the energy deposited in regions of interest.…”
Section: Methodsmentioning
confidence: 99%
“…These chamber types are specifically selected for this work as they are archetypal of classes of chambers available for photon beam reference dosimetry measurements for which k Q factors could be impacted by ICRU‐90 recommendations — graphite‐walled, plastic‐graphite‐walled, and plastic‐walled chambers. It is worth noting that in a recent survey on reference dosimetry practices about 40% of respondents used the PTW 30013 chamber for reference dosimetry of MV photon beams, making it the most commonly used chamber for these measurements . Since the ICRU‐90 recommendations are relevant only for graphite and water, results for these representative chambers will demonstrate the impacts of ICRU‐90 on k Q factors.…”
Section: Methodsmentioning
confidence: 99%
“…Surveys have been a useful tool in understanding and documenting the standard‐of‐care in various topics in radiotherapy physics . Over the past 5 yr, there have been over 250 surveys distributed mainly through the medical physics listserv covering varying topics of interest to clinical physicists (e.g., simulation practices, use of image guidance, and clinical workflow).…”
Section: Introductionmentioning
confidence: 99%
“…Recent surveys on reference dosimetry practices have shown that clinical physicists in North America are comfortable using the same cylindrical chambers that they use in photon beams for electron beam calibration . Given the additional complication associated with requiring a cross‐calibration procedure to use plane‐parallel chambers, the issues related to the behavior of plane‐parallel chambers and the demonstrated stability of reference‐class cylindrical chambers over decades, we ask the question in this work, “Can cylindrical reference‐class chambers be used for reference dosimetry of all electron beams, regardless of energy?…”
Section: Introductionmentioning
confidence: 99%